Prime Ministers on Twitter: Mateusz Morawiecki and Andrej Babiš during the 2019 European election campaign – two models of communication - Rawski, Tomasz; Budzyńska-Daca, Agnieszka; Rusin Dybalska, Renata (Political Preferences, 2021)
The aim of this paper is to analyse Twitter activity of Prime Ministers of Poland and of the Czech Republic, Mateusz Morawiecki and Andrej Babiš respectively, during the 2019 European Parliament election campaign with the special focus on their ways of creating, imposing and reproducing the campaign discourse. It examines especially the person-alization of the election campaign, namely using the election-related activities to promote their image. Also, the im-portance of hashtags as a strategy for building discursive styles is explored and ways of using political pretexts e.g. the Europe Day to introduce election themes are compared. In this context the answer to the following question pre-sents itself as a research challenge: to what extent PMs’ tweets impact the course and the dynamics of the campaign and to what extent it is just dry information, a press commentary?